Real time implementation of feedback linearization control based three phase shunt active power filter - GHADBANE, Ismail (Université de M'sila, 2018)
In This paper, we present an experimental study of feedback Linearization applied to regulate the DC bus voltage of three-phase shunt Active Power Filter (APF). The feedback linearization controller is introduced to improve tracking performance characteristics, power quality and minimized consumption of the reactive power. To identify the reference currents we used an algorithm based on the Self Tuning Filter (STF). We generate the firing pulses of the IGBT inverter by using a hysteresis current controller, which is implemented on an analog card..An experimental bench has been implemented. It consists an active filter parallel to IGBTs, a nonlinear a load RL, a dSPACE digital prototyping system (DS1104 development board) for generating the references of the harmonic currents and an analog card to realize the control of harmonic currents by hysteresis. The experimental results under steady state and transient conditions is illustrated with signal-flow graphs and corresponding analysis show the feasibility and the effectiveness of the designed active filter, associated with feedback Linearization controller capability in meeting the IEEE 519-1992 recommended harmonic standard limits.
Keywords: Harmonics, Shunt Active Filter, Feedback, Total Harmonic Distortion